Interactive Storytelling Dashboard for Climate Data to Improve Public Awareness: Dashboard Cerita Interaktif untuk Data Iklim guna Meningkatkan Kesadaran Masyarakat - Maharani, Bening Ayu; L, Joshua Roy D; Puja, Ichwan; K, Ramadhan Linggar; T, Nico Imanuel; Irawan, Bambang (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Climate change is a critical global issue requiring effective public education to foster awareness and engagement. Specific Background: Despite its urgency, public understanding of climate impacts remains limited, highlighting the need for innovative communication strategies. Knowledge Gap: Traditional approaches to disseminating climate information often lack interactivity and emotional resonance, reducing their effectiveness in engaging diverse audiences. Aim: This study aims to design and develop an interactive climate data dashboard that integrates data visualization with storytelling elements to enhance learning and public involvement. Results: Using historical climate datasets, interactive visualizations were created and evaluated through pre- and post-test assessments, showing a 35% increase in user understanding and stronger emotional engagement with environmental issues. Novelty: The integration of interactive storytelling with scientific data visualization represents a novel educational approach that moves beyond static information delivery. Implications: These findings suggest that combining data-driven insights with narrative elements can serve as an inclusive and impactful educational tool, offering substantial potential for climate change awareness campaigns and public engagement initiatives. Highlights: Integrates storytelling with data to enhance climate education. Improves understanding by 35% through interactive engagement. Offers a novel, inclusive tool for awareness campaigns. Keywords : Climate Change, Interactive Dashboard, Storytelling, Data Visualization, Public Awareness